EFEKTIVITAS KEBIJAKAN PEMBERIAN MODAL PELAKU USAHA MENENGAH KECIL DAN MIKRO DI KABUPATEN NAGAN RAYA - Juliansyah, Rollis; Yani, Meri (Puslatbang KHAN, 2024)
This study aims to measure the level of effectiveness of the community empowerment program through the provision of business capital and its impact on increasing income in micro-businesses in Suka Makmue Sub-district, Nagan Raya Regency, especially in the sewing business. The research method used is descriptive qualitative using questionnaires, interviews, observations, and literature studies as data collection techniques. The sample of this study was 25 respondents who were micro-business actors, especially tailors, who received capital loans from the empowerment program. The results showed that the provision of business capital through the community empowerment program has a high level of effectiveness in increasing micro-business income, especially in tailoring businesses in Suka Makmue District, Nagan Raya Regency. The level of effectiveness is calculated by comparing the realization of the capital received and the target income of the sewing business. In this study, the effectiveness level reached 124 percent, which indicates a very high level of effectiveness. The average capital realization of the empowerment program is Rp. 2,640,000, while the average income is Rp. 2,403,200. As a suggestion, for micro-entrepreneurs, the community empowerment program through the provision of capital can help in buying the equipment needed to open a business. This program is expected to be able to increase income and develop businesses to be more productive. In addition, this program also provides business opportunities and employment for the community.